Skuteczna ewangelizacja na przykładzie życia i działalności św. Eugeniusza de Mazenoda (1782–1861) - Biela, Bogdan (Studia Pastoralne, 2026)
In the post-synodal apostolic exhortation on the formation of priests in the circumstances of the present day Pastores dabo vobis, John Paul II described the new evangelisation as the most important and urgent task of the Church at the end of the second millennium. Therefore it calls for „a new zeal, new methods of preaching and giving testimony to the Gospel”, and most of all a new involvement of priests. A priest who combined all these factors was Eugene de Mazenod, the founder of the Missionary Oblates of Mary Immaculate. The testimony of his life and activity, in spite of the time that had passed, may be very inspiring even today. First of all it is because the 19th century France is not that different from the contemporary Western civilisation, especially when we realise, that the ideology of the French Revolution is the source of many contemporary cultural trends. Second of all, it is because in his activity one can find all the conditions of the effective evangelisation: a personal experience of salvation, ability to assess reality from the Gospel point of view, an apostolic zeal as the manifestation and testimony to love and propagating the spirituality of communion. John Paul II himself was convinced about exceptional values of this saint and found in him the example and the advocate of evangelisation of our times.